Anticancer activity of ethanol extracts of Polygala rosmarinifolia Wight & Arn whole plant against Dalton Ascites Lymphoma - Alagammal M, Packialincy M. and Mohan V.R. (Journal of Applied Pharmaceutical Science)
The present study aims to evaluate the antitumor activity of ethanol extract of whole plant of Polygala rosmarinifolia on DAL model in Swiss Albino mice. Evaluation of the antitumor effect of ethanol extract of whole plant of Polygala rosmarinifolia on tumor growth and host survival time was made by the study of the following parameters: tumor volume, viable and non viable cell count and life span of host. The results showed decrease in tumor volume and cell viability. Hematological studies revealed that, the Hb count decreased in DAL treated mice, whereas it was induced by the drug treated animals and showed an increase in Hb near to normal levels. The results suggested that the extracts of whole plant of Polygala rosmarinifolia exhibited significant antitumor activity on DAL bearing mice.
Keywords: Polygala rosmarinifolia, antitumor, lifespan, WBC.